Perancangan Pintu Otomatis Menggunakan Sensor PIR (Passive Infrared Receiver) Dimasa Pandemi Covid-19 - Tri Nurany; Angga Adiputra Wijaya; Muhammad Prakarsa Al Qard Saleh (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The purpose of this research is to design an automatic door using a PIR (Passive Infrared Receiver) Sensor during the Covid-19 Pandemic. This automatic door system is designed using automatic control combined with sensors and motors. The PIR sensor can detect a human coming to the door. This PIR sensor will send a signal to the controller. The controller will send processing information data to the motor so that it can open and close the door by itself. The door is a medium that is used as a way to enter or exit from one room to another. Generally, doors in public facilities are opened manually. During this pandemic, it is very vulnerable because the doorknob is touched by many people which allows the impact of Covid-19 transmission. The advantage of this innovation is that it can make it easier for people to open and close the door without physical contact with the door. The door will open automatically when there is a stimulus object (physical energy) that moves it. Regarding the current problems, the author proposes to make an automatic door design tool using a PIR sensor that can be implemented on the doors of public facilities in the hope of helping reduce the risk of transmission and prevent wider spread.